Islamic economics basic concepts, new thinking and future directions - Egri, Taha; Kızılkaya, Necmettin (Cambridge Scholars Publishing, 2015)
Studies conducted in the field of Islamic economics lose their relevance over time. Although there are various conceptualizations, such as 'the economy of Islam', 'the Islamic economy', 'Islamic economics', 'Islamic finance', and so on, it has become difficult to clarify these ideas with regards to the intention with which these concepts are used, their points of reference, and the kind of power they have.